PKR Stimulates NF-κB Irrespective of Its Kinase Function by Interacting with the IκB Kinase Complex - Bonnet, Marion C. (American Society for Microbiology, 2000)
The interferon (IFN)-induced double-stranded RNA-activated protein kinase PKR mediates inhibition of protein synthesis through phosphorylation of the α subunit of eukaryotic initiation factor 2 (eIF2α) and is also involved in the induction of the IFN gene through the activation of the transcription factor NF-κB. NF-κB is retained in the cytoplasm through binding to its inhibitor IκBα. The critical step in NF-κB activation is the phosphorylation of IκBα by the IκB kinase (IKK) complex. This activity releases NF-κB from IκBα and allows its translocation to the nucleus. Here, we have studied the ability of PKR to activate NF-κB in a reporter assay and have shown for the first time that two catalytically inactive PKR mutants, PKR/KR296 and a deletion mutant (PKR/Del42) which lacks the potential eIF2α-binding domain, can also activate NF-κB. This result indicated that NF-κB activation by PKR does not require its kinase activity and that it is independent of the PKR-eIF2α relationship. Transfection of either wild-type PKR or catalytically inactive PKR in PKR(0/0) mouse embryo fibroblasts resulted in the activation of the IKK complex. By using a glutathione S-transferase pull-down assay, we showed that PKR interacts with the IKKβ subunit of the IKK complex. This interaction apparently does not require the integrity of the IKK complex, as it was found to occur with extracts from cells deficient in the NF-κB essential modulator, one of the components of the IKK complex. Therefore, our results reveal a novel pathway by which PKR can modulate the NF-κB signaling pathway without using its kinase activity.